The effect of halal labeling on the performance of small and medium enterprise (SME) in medan city - Ichsan, Reza Nurul; Hartin Nst, Venny Fraya; Nasution, Lukman; Hutabarat, Lamminar (Jurnal Mantik, 2024)
Indonesia has the largest Muslim market share in the world, with a large percentage of the Muslim population, the availability of foodstuffs is certainly an important factor in meeting the food consumption needs of the Indonesian population, not only good and healthy food but also halal. This study aims to determine the effect of halal labeling on the performance of Small and Medium Enterprise (SME) in Medan City. The population in this study is 406 business actors. This study used a quantitative approach. Data collection techniques used using questionnaires/questionnaires. Questionnaires were given to business actors in Medan City. Based on the results of the study that halal labeling statistically has a significant effect on the performance of Small and Medium Enterprise (SME). Based on the results of the study that halal labeling statistically has a significant effect on the performance of Small and Medium Enterprise (SME). Based on the results of the coefficient of determination test that halal labeling has a strong relationship (correlation) of 86.4%. The amount of adjusted R2 produced 0.743 means that 74.3% of the independent variable contributes an effective influence on the dependent variable while the remaining 25.7% is influenced by other factors